Revealing the pathways of catalyst deactivation by coke during the hydrodeoxygenation of raw bio-oil - Cordero-Lanzac, Tomás; Palos, Roberto; Hita, Idoia; Arandes, José M.; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Bilbao, Javier; Castaño, Pedro (Elsevier, 2018)
Virtually all processes aiming for fuels and chemicals from biomass entail no less than one step for removing oxygen by hydrodeoxygenation (HDO). The bottleneck of HDO is the formation of deactivating carbonaceous species on the catalyst surface. In this work, we have studied the deactivation pathways of catalysts based on noble metal nanoparticles (Pt-Pd) supported on mildly acid supports during the HDO of raw bio-oil. At conditions of accelerated deactivation, monitoring the evolution with time on stream of hydrocarbon and oxygenated compounds in the reaction medium, the intermediates on the catalyst surface and the nature-location of deactivating species, two parallel deactivation routes have been revealed: the deposition of (i) thermal or pyrolytic lignin from alkylmethoxy phenols, on the catalyst mesopores and favored at low temperature, and; of (ii) aromatic coke from polycyclic aromatic hydrocarbons, starting on the catalyst micropores through condensation reactions and promoted by acidic sites and high temperature. Nevertheless, catalyst deactivation can be controlled within limits at harsh temperature conditions (450 °C) due to the preferential HDO of alkyl(methoxy) phenols into aromatics and the formation-hydrocracking steady state of the aromatic precursors of coke.
Keywords: Carbón activado; Desactivación; Bio-oil; Hidrodeoxigenación; Carbones activos; Ingeniería química